Efecto antimicrobiano in vitro de extractos de Caesalpinia spinosa sobre cepas de Staphylococcus aureus resistentes a antibióticos betalactámicos - Villavicencio Coral, Bryan Darío (2021)
Objective. To determine the antimicrobial effect of ethanolic extracts from Caesalpinia spinosa against penicillin and methicillin resistant strains of Staphylococcus aureus penicillin and methicillin. Methods. S. aureus ATCC 11632 and 33592 strains were used, ethanolic extracts from C. spinosa leaves and pods were obtained by maceration at concentrations of 25%, 50%, 75% and 100%. The Kirby-Bauer method was used, where filter paper discs were loaded with leaf, pod and seed extracts and deposited on the medium, inoculated with a 0.5 McFarland suspension of S. aureus. Ampicillin discs were used as positive control and ethanol-impregnated discs as negative control. After 24 hours, the diameters of the halos were measured with a Vernier caliper. Results. Haloes up to 18 mm in diameter with 100% leaf extracts, 17 mm with pod extracts and 14 mm with seed extracts were recorded against S. aureus ATCC 33592; for ATCC strain 11632, haloes up to 14 mm with 100% leaf and pod extracts and up to 8 mm with seed extracts were recorded.  The ANOVA test indicated that there were significant differences between the inhibition halos obtained with the different types of extracts, at different concentrations. Conclusion. It was determined that all C. spinosa extracts possess antimicrobial activity against the two strains studied, with a pattern directly proportional between the effect and concentration.